2019
DOI: 10.14746/ssllt.2019.9.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment as a key to success? Links between e-tandem language learning and tertiary students’ foreign language enjoyment

Abstract: This paper reports on crossing borders virtually via an e-Tandem scheme and presents the findings of a study, in which students of English from an Austrian university were paired with students of German from the UK and the USA. Drawing on data from 19 in-depth interviews, the study aims to identify links between e-Tandem language learning and foreign language enjoyment (FLE) (Dewaele & MacIntyre, 2014, 2016). A category-based qualitative text analysis (Kuckartz, 2014) revealed that a majority of the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
1
23
0
3
Order By: Relevance
“…It has positive subjective experiences, positive individual traits, and positive institution as its three main pillars ( Seligman and Csikszentmihalyi, 2000 ; Dewaele et al, 2019 ). Since positive psychology was introduced into SLA a few years ago ( MacIntyre and Mercer, 2014 ), it has instigated a number of studies on positive emotions in SLA, particularly enjoyment (e.g., Jin and Zhang, 2018 , 2019 ; Resnik and Schallmoser, 2019 ; Dewaele and Dewaele, 2020 ). More recently, researchers have attempted to investigate ways of anxiety reduction from a positive psychology perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has positive subjective experiences, positive individual traits, and positive institution as its three main pillars ( Seligman and Csikszentmihalyi, 2000 ; Dewaele et al, 2019 ). Since positive psychology was introduced into SLA a few years ago ( MacIntyre and Mercer, 2014 ), it has instigated a number of studies on positive emotions in SLA, particularly enjoyment (e.g., Jin and Zhang, 2018 , 2019 ; Resnik and Schallmoser, 2019 ; Dewaele and Dewaele, 2020 ). More recently, researchers have attempted to investigate ways of anxiety reduction from a positive psychology perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participants in this research were international students who study and live in an English-speaking country, thus their self-reported levels of listening anxiety and enjoyment likely targeted emotions both inside and outside the classroom. Considering that high exposure to the target culture might alleviate language anxiety and increase enjoyment (Aneiro;1989;Resnik & Schallmoser, 2019), students who study the L2 in their home country may use the L2 only in classrooms. Thus, they may have different emotional experiences and different patterns of strategy use.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…MIM serves as social and cultural artifact to grant the impetus for language learning by stimulating multitudes cognitive and metacognitive processing within communicative setting (Resnik & Schallmoser, 2019). To that end, MIM serves as the catalyst for linguistic and cognitive undertaking.…”
Section: Team-based Mobile Learning Via Mimmentioning
confidence: 99%